2017
DOI: 10.1186/s12877-017-0587-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia with lifestyle and family function among community-dwelling Chinese aged 60 years and older

Abstract: BackgroundSarcopenia is defined as the age-related decline in skeletal muscle mass and function. The risk factors and causes of sarcopenia must be identified to develop prevention and treatment strategies for this syndrome. Our aim was to examine the association between sarcopenia with lifestyle and family function among community-dwelling Chinese people aged 60 years and older.MethodsWe conducted this study to evaluate sarcopenia among 834 community-dwelling Chinese individuals aged ≥60 years using the Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 25 publications
4
71
0
4
Order By: Relevance
“…Of these, three studies examined the relationship between meat intake (red meats, poultry, and processed meats) and muscle mass and function [ 21 , 22 , 23 ]; five examined the intake of fruit and vegetables in relation to sarcopenia and muscle function [ 24 , 25 , 26 , 27 , 28 ], and eight studies investigated the link between multiple whole foods and various muscle-related outcomes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The individual whole foods were: fatty fish, white fish and shellfish, legumes, soy, nuts and seeds, eggs, and the components of the Nordic Dietary Score (NDS), including Nordic cereal (rye, oats, barley) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Three studies investigated the association between dairy intake (including yogurt and cheeses) and muscle mass and function [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three studies examined the relationship between meat intake (red meats, poultry, and processed meats) and muscle mass and function [ 21 , 22 , 23 ]; five examined the intake of fruit and vegetables in relation to sarcopenia and muscle function [ 24 , 25 , 26 , 27 , 28 ], and eight studies investigated the link between multiple whole foods and various muscle-related outcomes [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The individual whole foods were: fatty fish, white fish and shellfish, legumes, soy, nuts and seeds, eggs, and the components of the Nordic Dietary Score (NDS), including Nordic cereal (rye, oats, barley) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Three studies investigated the association between dairy intake (including yogurt and cheeses) and muscle mass and function [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…To assess diet, ten studies used food frequency questionnaires (FFQ) [ 24 , 27 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 38 ], four studies employed diet histories [ 21 , 23 , 25 , 39 ], one used 3-day diet record [ 36 ], one 24-h dietary recall [ 22 ], two used lifestyle questionnaire [ 26 , 32 ], and one study used a single question for a specific food group [ 28 ]. Muscle-related outcomes varied across the studies; six examined muscle mass (total, lean, appendicular, skeletal muscle index, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…However, in comparison with the Chinese general population, the family APGAR score of TB patients was lower. For example, Cheng et al reported that the family APGAR score was 8.08 (SD = 2.18) for 1052 adult residents aged 15 years and older in Hubei Province [27], and Hai et al showed that the score was 8.00 (SD = 0.92) for 834 community-dwelling Chinese individuals aged ≥60 years [28]. This illustrates that TB patients' family function is somewhat impaired, and improving it would be an effective strategy to combat their stigma.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally believed that score 0-3 indicated severe family dysfunction, 4-6 indicated moderate family dysfunction, and 7-10 indicated good family function. The Chinese version of APGAR has been widely applied in China with excellent validity and reliability [42,43]. In this research, Cronbach's α of the scale was 0.874.…”
Section: Family Functionmentioning
confidence: 76%